Electrochemical sensor using chitosan-based nanomaterials modified screen printed carbon electrode for bisphenol a detection - Mohd Daud, Nor Faezah (2022)
Bisphenol A (BPA) is an organic compound found in plastic products that used every day. It is mostly transferred into foods and drinks including water bottles, lining of food cans, and dental fillings. It is known that BPA is considered as an endocrine-disrupting compound which related to various kinds of health concerns such as the development of cancers and reproduction problems. Thus, the development of a reliable analytical approach for the detection of BPA is an urgent issue. In this study, electrochemical sensor based on modification of screen-printed carbon electrode (SPCE) with two fabricated sensor which are carbon dots-chitosan (CDs-CS) and gold nanoparticles/carbon dots-chitosan (AuNPs/CDs-CS) have been explored for the detection of BPA. Each sensor was prepared using drop casting technique. The detection of BPA using these sensors was studied employing differential pulse voltammetry (DPV). Characterization was done by Field emission scanning electron Microscopy (FESEM) and Energy Dispersive X-Ray Spectroscopy (EDX), High- Resolution Transmission Electron Microscopy (HRTEM) and Fourier Transform Infrared Spectroscopy (FTIR). FTIR spectra for CDs-CS shows peak at 1648 cm−1, 1411 cm−1 and 1038 cm−1 for vibration of C=O hydroxyl group on CDs. New peak at 1100 cm−1 are related to the strong C-O stretching of AuNPs/CDs- CS. Optimum parameter for the sensor development such as CS concentration of 1% (m/v) and CDs : CS ratio of 1/1 (v/v), and 7 μL of CDs-CS volume drop casted on SPCE for first sensor, the volume ratio of the composite CDs-CS and AuNPs was 1 : 1.5 (v/v) and 3 μL of AuNPs/CDs-CS drop casted on SPCE for the second sensor was evaluated to improve the performance of the developed sensors. The results showed that SPCE modified with CDs-CS composite and AuNPs/CDs-CS has a great electrocatalytic features for detecting BPA in the concentration range of 0.4 μM to 10 μM with sensitivity of 0.46 μA/μM (R² = 0.9911) and limit of detection (LOD) of 0.37 μM for the CDs-CS/SPCE sensor while concentration range of 0.4 μM to 10 μM of BPA with sensitivity of 0.28 μA/μM (R² = 0.9937) and LOD of 0.1 μM for the AuNPs/CDs-CS/SPCE sensor. Good reproducibility of the sensors with relative standard deviation (RSD) 3.66 % (n = 15) for CDs-CS/SPCE while 1.35 % (n = 15) for AuNPs/CDs-CS/SPCE, respectively. For storage stability, both sensors retained their performances to 79.1% and 90.3% for CDs-CS/SPCE and AuNPs/CDs-CS/SPCE of their original response after a month of storage. The interferences studies of these sensors showed that there is no significant interfering effect towards phenol, 2,4- dinitrophenol, 4-chlorophenol, K+,Cu2+, Cl−, and SO4 2− even with 10-fold higher concentration compared to BPA. The fabricated sensors were successful applied for the determination of BPA in tap water of disposable plastic cup and PVC mineral water bottle with satisfactory recovery results from 96.21% to 101.40% for CDs-CS/SPCE while 98.89% to 100.37% for AuNPs/CDs-CS/SPCE. These findings suggest that the developed sensors have a promising potential for the detection of BPA in real sample for environmental monitoring and industry quality control.